Active surveillance of adverse drug reactions in patients with rheumatoid arthritis in a tertiary care teaching hospital - R., Nalini; D., Keerthi; B., Meenakshi; J., Ezhil Ramya; ., Vidhya (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drugs used in the treatment of rheumatoid arthritis show significant toxicity and morbidity. The objective of the study was to evaluate the nature and incidence of adverse drug reaction in patients with rheumatoid arthritis on anti-rheumatic drugs and to assess the causality and severity of the documented adverse drug reactions. Methods: The prospective observational study was done for two months in rheumatology outpatient department. All patients were interviewed for basic details, treatment history and adverse drug reactions and were recorded. Causality assessment and severity assessment of the recorded adverse drug reactions were done. Results: About 283 patients attended the rheumatology out-patient department during the two months period out of which 57 patients had one or more adverse drug reaction. The incidence of adverse drug reaction observed in rheumatology out-patient department to anti rheumatic drug was 20.14%. A total of 145 adverse drug reactions were noted in 57 patients. The most common adverse drug reaction reported was epigastric pain (6.89%) followed by headache and dyslipidemia (6.25%). The most common system associated with adverse drug reaction was gastrointestinal system (29.66%) followed by central nervous system and cardiovascular system (15.86%). Reported adverse drug reactions were assessed for causality and maximum belonged to probable (66.9%). Severity assessment revealed that most of the adverse drug reactions were mild (74.48%) in nature. Conclusions: Active surveillance for adverse drug reactions to anti rheumatic drug in patients with rheumatoid arthritis will allow early detection of adverse drug reactions and timely intervention to provide maximum benefit to the patients.